Evaluation of the Effectiveness of Educational Resource Management (Human Resources and Finance) in Supporting Curriculum Implementation at SMP Negeri 3 Kotabaru - Assyakhirah Nur Ridha; Muhammad Hafiudin Rizaldi; Yeslin Anjelina Terayanti; Muhammad Rizhan; Sahdat Sahdat; Aslamiah Aslamiah; Ahmad Suriansyah (FKIP - Universitas Riau, 2026)
This study aims to evaluate the effectiveness of educational resource management, particularly human resources (HR) and financial resources, in supporting curriculum implementation at SMP Negeri 3 Kotabaru. The research focuses on how the principal applies data-driven, reflective, and collaborative management approaches to optimize teacher potential and ensure transparent and accountable financial management. A qualitative descriptive method was employed, with data collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that the effectiveness of resource management at SMP Negeri 3 Kotabaru is achieved through three main strategies: (1) reflection- and coaching-based HR management that encourages teachers’ self-evaluation and continuous professional development; (2) humanistic leadership emphasizing emotional regulation, empathy, and dialogic communication to foster a collaborative work culture; and (3) transparent and participatory financial management involving all school members in budgeting and evaluation processes. This study concludes that the effectiveness of HR and financial management is not solely determined by the principal’s technical managerial skills but also by reflective, ethical, and collaborative leadership. Such a management model fosters a sustainable culture of quality and strengthens the successful implementation of the Merdeka Curriculum.